Wasathiyah Approach in Education: An Effective Strategy to Counter Radicalism and Extremism - Salsabila, Mauhubah Althaf (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
This article discusses the important role of education in facing the challenges of the spread of radicalism and intolerance in the educational environment. This research highlights the need to strengthen moderate religious values, such as Wasathiyah Islam, through a systematic and integrated learning approach. Using the critical discourse analysis method, this research identifies strategies to prevent the influence of extremism and intolerance while building a culture of inclusiveness and tolerance. The results show that the values of moderation, tolerance and brotherhood contained in the teachings of Wasathiyah Islam have strong relevance to be applied in education. This strategy includes the integration of these values into the curriculum, cross-subject learning, and extracurricular activities. In addition, this research emphasizes the importance of involving all stakeholders, including teachers, students and parents, to create a conducive and harmonious learning environment. Consistent application of these values is expected to build students' critical awareness of the dangers of radicalism while strengthening their sense of community and social solidarity. Thus, education not only acts as a means of transferring knowledge, but also as an important instrument in maintaining diversity and building an inclusive future.